Base Editors for Citrus Gene Editing - Huang, Xiaoen; Wang, Yuanchun; Wang, Nian (Frontiers in Genome Editing, 2022)
Base editors, such as adenine base editors (ABE) and cytosine base editors (CBE), provide alternatives for precise genome editing without generating double-strand breaks (DSBs), thus avoiding the risk of genome instability and unpredictable outcomes caused by DNA repair. Precise gene editing mediated by base editors in citrus has not been reported. Here, we have successfully adapted the ABE to edit the TATA box in the promoter region of the canker susceptibility gene LOB1 from TATA to CACA in grapefruit (Citrus paradise) and sweet orange (Citrus sinensis). TATA-edited plants are resistant to the canker pathogen Xanthomonas citri subsp. citri (Xcc). In addition, CBE was successfully used to edit the acetolactate synthase (ALS) gene in citrus. ALS-edited plants were resistant to the herbicide chlorsulfuron. Two ALS-edited plants did not show green fluorescence although the starting construct for transformation contains a GFP expression cassette. The Cas9 gene was undetectable in the herbicide-resistant citrus plants. This indicates that the ALS edited plants are transgene-free, representing the first transgene-free gene-edited citrus using the CRISPR technology. In summary, we have successfully adapted the base editors for precise citrus gene editing. The CBE base editor has been used to generate transgene-free citrus via transient expression.